2017
DOI: 10.1002/bse.1988
|View full text |Cite
|
Sign up to set email alerts
|

Market Orientation and FIRMS' Environmental Innovation: The Moderating Role of Environmental Attitude

Abstract: Drawing on market orientation theory, innovation theory and the theory of reasoned action, this paper integrates market orientation, environmental attitude and firms' environmental innovation into a model to establish a relationship among these three variables. By taking 247 manufacturing firms in China as the research sample and by analyzing the data using SPSS19.0, we found that customer and competitor orientation have a significant and positive impact on firms' environmental innovation, while the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
4

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 51 publications
(57 reference statements)
1
45
0
4
Order By: Relevance
“…This variable is often involved in social psychological theories/models as a considerable influence on one's decision‐making process and behaviour (Perugini & Bagozzi, ). This concept is also frequently employed when explicating one's eco‐friendly decision‐making and behaviour (Han, ; Jansson, ; Liao, ; Matthies, Selge, & Klöckner, ; Sun, The, & Linton, ). In the present study, attitude towards eco‐friendly behaviour at hotels refers to the degree to which guests have a positive/negative assessment/appraisal of environmentally responsible behaviour (e.g., towel reuse, water conservation) while staying at hotels.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This variable is often involved in social psychological theories/models as a considerable influence on one's decision‐making process and behaviour (Perugini & Bagozzi, ). This concept is also frequently employed when explicating one's eco‐friendly decision‐making and behaviour (Han, ; Jansson, ; Liao, ; Matthies, Selge, & Klöckner, ; Sun, The, & Linton, ). In the present study, attitude towards eco‐friendly behaviour at hotels refers to the degree to which guests have a positive/negative assessment/appraisal of environmentally responsible behaviour (e.g., towel reuse, water conservation) while staying at hotels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although studies in the extant literature do not always offer consistent results regarding the influence of attitude, findings in the studies in general revealed that attitude towards behaviour played an essential role in generating pro‐environmental intention, and had significant interrelationships with other variables triggering such intention (Han, ; Liao, ; Matthies et al, ; Perugini & Bagozzi, ). In the conventional tourism sector, Han () showed that the degree to which travellers feel a personal moral obligation to take an eco‐friendly action, which is a significant function of attitude towards the eco‐friendly behaviour, is directly and positively connected to their intention to select a pro‐environmental tourism product.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study selected the size and age of a firm as control variables. The number of employees was used to measure the size of the firm, and the number of years since the establishment of the firm was used to measure the age of the firm (Deloof, Lagaert, & Verschueren, ; Dibrell, Craig, & Hansen, ; Liao, ). Logarithmic processing was performed on both variables.…”
Section: Methodsmentioning
confidence: 99%
“…When companies conform to prevailing norms, they can benefit from easier access to resources. Companies can also manipulate the expectations of their environment (Liao, ; Ruef & Scott, ) in their favor through social influence (Lorenz, Rauhut, Schweitzer, & Helbing, ) or economic influence. Such influence could be more effective when companies have an embedded rather than an arms‐length relationship with stakeholders (Jones, Harrison, & Fleps, ).…”
Section: Theoretical Framework Definitions and Hypothesesmentioning
confidence: 99%